Analysis of the Effects of the Pre-Employment Card Program Trainings on Employment Statuses in Java - Renata Intan Avicenna; Al Muizzuddin Fazaalloh (Journal of Development Economic and Social Studies, 2026)
Java Island serves as Indonesia’s economic center and is home to the country’s largest population. At the same time, it records the highest unemployment rate at the national level. To address this issue, the government introduced the Pre-Employment Card Program, which aims to improve workforce skills through training and financial incentives. Although several previous studies have examined the effectiveness of the Pre-Employment Card Program, there remains limited information regarding the extent to which its training component improves employment opportunities in Java. Therefore, this study aims to analyze the impact of the Pre-Employment Card Program training on employment status in Java. This study employs a quantitative research method using data from SAKERNAS 2023. The total sample consists of 211,872 individuals. The data are analyzed using binary logistic regression to estimate the probability of individuals securing employment. The findings of this study reveal that the Pre-Employment Card Program training has a positive and statistically significant effect on employment status in Java Island.